2010
DOI: 10.1080/18811248.2010.9720975
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Countercurrent Gas-Liquid Flow in a PWR Hot Leg under Reflux Cooling

Abstract: In reflux cooling, the steam generated in the reactor core and the water condensed in a steam generator form a countercurrent flow in a hot leg. In order to investigate flow patterns in the hot leg under countercurrent flow conditions, countercurrent air-water tests were previously conducted using a 1/15 th scale model of a PWR hot leg. Numerical simulation results for the tests using a three-dimensional twofluid model in FLUENT6.3.26, implemented with an appropriate set of correlations for the gas-liquid inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…We found that the two-fluid model could reproduce CCFL characteristics under low pressure conditions and we confirmed that those in the hot leg could be well correlated with the Wallis parameters [13,14]. The two-fluid model, however, did not give good results for high pressures.…”
Section: Introductionmentioning
confidence: 49%
See 2 more Smart Citations
“…We found that the two-fluid model could reproduce CCFL characteristics under low pressure conditions and we confirmed that those in the hot leg could be well correlated with the Wallis parameters [13,14]. The two-fluid model, however, did not give good results for high pressures.…”
Section: Introductionmentioning
confidence: 49%
“…Based on the CCFL data from air-water tests with the diameter of 50 mm [9] and CCFL characteristics calculated for a full-scale model with the diameter of 750 mm using the two-fluid model, we proposed the following correlation for low pressures below 0.3 MPa [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors previously implemented numerical simulations using a two-fluid model in FLUENT 6.3.26 with an appropriate set of correlations for the gas-liquid interfacial drag coefficients, and carried them out for full-scale PWR plant conditions. (10) The predicted CCFL characteristics were well correlated with Wallis parameters for system pressures below 0.3 MPa, and showed no difference between different fluid property systems. On the other hand, the experiments conducted in the full-scale Upper Plenum Test Facility (UPTF) with steam/saturated water at pressures 0.3 and 1.5 MPa showed an apparent difference in CCFL curves at pressures between 0.3 and 1.5 MPa, (6) though the effects of fluid properties were not clearly mentioned.…”
Section: Introductionmentioning
confidence: 67%
“…Air at pressure 0.1 MPa was used for the gas phase in the simulations. Figure 15 compares predicted CCFL characteristics on the Wallis parameter diagram, in which the fitting curve of the measured CCFL correlation for air/water experiments in the same 1/15 th hot leg (10) is also shown. There is no significant difference in the predicted CCFL characteristics between the saturated water at 264 o C and the water at room temperature, while there is a clear difference between the GW 60 wt% and the water at room temperature.…”
Section: Discussionmentioning
confidence: 99%